Chemical Constituents from Uapaca guineensis (Phyllanthaceae), and the Computational Validation of Their Antileishmanial and Anti-inflammatory Potencies - Gervais Mouthé Happi; Mireille Towa Yimtchui; Sikiru Akinyeye Ahmed; Shina Salau; Liliane Clotilde Dzouemo; Klev Gaïtan Sikam; Jean Duplex Wansi (Journal of Chemistry)
From the chemical investigations of the root bark of Uapaca guineensis, nine distinct compounds (1–9) have been isolated and characterized as lupeol, betulin, betulinic acid, β-amyryl acetate, physcion, quercetin, rutin, β-sitosterol, and β-sitosterol-3-O-β-D-glucopyranoside, respectively. The structures of all the isolated compounds have been established using their NMR data as well as the comparison of those data with the ones reported in the literature. Interestingly, to the best of our knowledge, except for the lupane-type triterpenoids (1–3) and compounds 4 and 9, all the other compounds are reported for the first time from this genus. Since the plant is widely used for the treatment of skin diseases, leishmaniasis and inflammatory diseases, the antileishmanial and anti-inflammatory potencies of all the isolated compounds have been computationally validated through their ability to inhibit the receptors 1QCC and 2XOX (for the antileishmanial studies) and 6Y3C and 1CX2 (for the anti-inflammatory studies). Furthermore, the ADMET studies of compounds have been done to evaluate their drug-likeness. Results demonstrate that all the isolated compounds showed a better affinity for both receptors’ binding sites than the standard drugs miltefosine and aspirin. Moreover, the compounds would not cause addiction when used as lead molecules whereas, aspirin is predicted to violate the BBB over a long term of usage as a drug. This study gives additional information on the chemistry of U. guineensis and its classification as a potential source of good leads for the development of potent antileishmanial and anti-inflammatory drugs.